Phytochkmical profiling antioxidant activities and essential oil, constituents of Androgkaphis Paniculata (2018)
Oxidative stress is involved in the pathogenesis of various diseases which lead to urgent- need to investigate new, safe and effective source of antioxidant agents. This research proposed to investigate in-vitro and phytochemical constituent of the plant Ancirographis paniculatei using phytochemical analysis, GC/MS, DPPH, ABTS, FRAP and NO. Phytochemica! analysis of Anclrographis paniculata revealed the presence of tannins, total fiavonoids, total phenol, total flavonols, and total proanthocyanidins. GC/MS analysis of essential oil of AP identified one major compound name benzencpropanoic acid clucked at 3.296 retention time and 0,74 area percentage. The ferric reducing potential of the extracts was concentration dependent and significantly different from that of rutin and vitamin E. The% inhibition ofABTS by the ethanol leaf extract o?A nclrographis paniculata was concentration dependent and compared favourably well with the rutin and vitamin E, in DPPH scavenging assays, the ICy50 value of the ethanol leaf extract of Andrographis paniculata was < 0.025 mg/ml, while IC50 of rutin and Vitamin E were < 0.025 mg/ml and 0.68mg/ml. Nitric oxide ICS, for extract is 1,05mg/ml, Vitamin E is 1.2 mg/ml, and rutin is < 0.025 mg/ml. The present study showed high level of radical scavenging activity by ethanol leaf .extract of Andrographis paniculata with higher antioxidant activities than Vitamin E but less than that of rutin. This show that Andrographis paniculata has antioxidant properties and the plant could be used in the prevention and treatment of diseases associated with oxidative stress.